Operational Risks For Highway Projects In Malaysia. - Mohamed Ghazali, Farid Ezanee (2009)

(untitled)
The Malaysia Highway Authority (MHA) was established by the Government in 1980 for the purpose of designing, constructing and maintaining toll highways in Malaysia that include the North-South Expressway and the Penang Bridge, which were procured using the publicly-funded traditional procurement. However following a recession in the mid 80’s, the operations of these tolledhighways had been privatized to ensure that their operational services continue through private financing as a result of long-term concession agreement concurred between the Malaysian Government and private operators. The change in the contract strategy for highway projects in Malaysia would have a great tendency to dictate a significant risk exposure towards the key parties involved, particularly the Malaysian Government as project principal, unless operational risks are clearly identified and managed via appropriate mitigation measures prior to a contract signing.